A Qualitative Analysis of the Nature and Causes of Truancy Among the University Students in Tripoli, Lebanon - Maya Bazhouni (European Scientific Journal, ESJ, 2019)
Class attendance and involvement in school activities are essential for academic achievement. Nonetheless, truancy, chronic absenteeism, or skipping more than 20% of lectures per semester, is a major problem globally. Numerous investigations have focused on the prevalence and impacts of truancy, but none have been conducted in Lebanon. Therefore, the purpose of the present research was to fill the gap in the literature and explore the nature and causes of truant behaviors among students in two universities in Tripoli, Lebanon. The study espoused a qualitative descriptive design, which entailed face-to-face semi-structured interviews with ten purposefully sampled respondents. The gathered data was analyzed thematically, leading to the identification of two major themes and four sub-themes. Notably, family dynamics, the instructional techniques and lecture content, and the student qualities, particularly conscientiousness, influenced the decision to attend or skip classes. The sampled students concurred that there was a need for training professors to diversify their teaching approaches, and subsequently, reduce boredom and truancy.